EVALUATION OF THE ANTI-MYCOBACTERIAL, ANTI-OXIDATIVE AND ANTI-PROLIFERATIVE ACTIVITIES OF RUBIA CORDIFOLIA ETHANOLIC LEAF EXTRACT SUB-FRACTIONS IN HUMAN LYMPHOCYTES AND NEUTROPHILS - ME, Makgatho; W, Nxumalo; E, Ndaba; Masilo, C; Tsindane, F; Sedibane, Ml (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background. Rubia cordifolia has been used to treat various diseases and exhibits antimicrobial, anti-inflammatory,analgesic and antidiarrheal activities. The plant has not been investigated for its anti-mycobacterial activity againstvirulent tuberculosis strains as well as cytotoxic and anti-oxidant activities in mononuclear cells and neutrophils.Methods. Ethanolic and dichloromethane leaf extract fractions of Rubia cordifolia (0.2- 125μg/ml) were screened foranti-mycobacterial activity using a fluorescent microplate assay. The anti-oxidant activity of the fractions was testedusing the radical scavenging assay, while their cytotoxicity to lymphocytes was measured using the WST-8 assay.Reactive oxygen species production by neutrophils exposed to fractions was tested using Cell Meter™ FluorimetricROS Assay kit.Results. The ethanolic leaf fractions exhibited overall superior anti-mycobacterial activity than the dichloromethanegroup and were further screened for anti-oxidant and cytotoxic activities. Ethanolic sub-fractions K2F-3.2, K2F-3.3 andK2F-3.4 showed significant antioxidant activities at concentration of 50 μg/ml to 200 μg/ml and higher in both the cellfree-based radical scavenging activity and total reactive oxygen species production assays. For lymphocytes, the testagents showed anti-proliferative activity at 25 μg/ml to 200 μg/ml for sub-fraction K2F-3.3B and 50 μg/ml to 200μg/ml for agents K2F-3.2 and K2F-3.4.Conclusion. The current study is the first to record the in vitro anti-mycobacterial, anti-oxidant and cytotoxic activitiesof Rubia cordifolia plant leaf extract sub-fractions using the given experimental setups and further research activities toidentify the bioactive components are to be pursued.